A new method of control of coherent structures in vortex apparatuses - Turick, Vladimir; Kochin, Viktor; Kochina, Mariia (КНУБА : ІТГІП, 2018)
A new method for direct control of energy-intensive coherent vortex structures (ECVS) in a vortex chamber is provided with stable vortex wires, which are descended from the lateral edges of a small elongated wing which is mounted in the inlet nozzle of the chamber. The main task is to determine the reaction of the ECVS in the dead-end ("passive") and the flow ("active") parts of the chamber to the control actions of the nozzle exciter is solved. The efficiency of the principle of mutual susceptibility of vortex structures on the processes of controlling coherent structures for bounded flows in the fields of centrifugal forces is experimentally proved. The observed phenomenon of "pumping" energy of pulsations from small vortices to larger ones allows it to be used to control aerodynamic and hydrodynamic processes of mixing and thermal processes in vortex process and energy devices.
Keywords: coherent vortex structures; control of the flow structure; vortex chamber; wing type vortex generator; mutual susceptibility of vortices; 533.6.08: 532.527